Perfekcionistička samoprezentacija i zavisnost od pametnog telefona: Uloga motiva i ponašanja na društvenoj mreži Instagram - Goljović, Nikola (Psihološka istraživanja, 2024)
This research investigates the link between perfectionistic self-presentation and smartphone addiction, with a particular focus on the driving motives and behavioral patterns associated with Instagram use. Engaging a diverse sample of 313 individuals, predominantly female (58.5%), ranging from 18 to 39 years old (M = 23.67; SD = 4.77), we meticulously examined the factors that might underpin this dynamic. As measures in this paper we used Perfectionistic Self-Presentation Scale, Motives for Instagram Use Scale, Instagram Usage Questionnaire, and Smartphone Addiction Short Scale. Path analysis not only underscored a direct influence of perfectionistic self-presentation on smartphone addiction but also unveiled a series of partial mediating effects. Our findings indicate that perfectionistic self-presentation informs the motives driving Instagram use. These motives, in turn, shape the specific ways in which users engage with the platform, which ultimately contributes to the likelihood of smartphone addiction. The mediating role of Instagram use is dissected, shedding light on the sequential process from PSSP to addiction. Interpreted through the lens of the Perfectionistic Social Exclusion Model and the Uses and Gratifications Theory, our results offer a richer understanding of how social media can fulfill perfectionistic tendencies and contribute to addictive behaviors. The study emphasizes the need for a multidimensional approach to examining social media’s psychological impact, proposing a bridge between individual predispositions and broader social phenomena. These insights not only contribute to academic discourse but also hold implications for mental health practitioners and policy makers concerned with the growing intersection of social media use and psychological well-being.